A school like mine a celebration of schools around the world - Smith, Penny (Children's author); Shalev, Zahavit (New York DK Publishing, 2016)
Introduces children from around the world and discusses where they live, how they play, and what their schools are like
The Americas -- Africa -- Europe -- Asia -- Australasia
"First edition written and edited by Penny Smith and Zahavit Shalev."
Includes index
1
Keywords: Children -- Cross-cultural studies -- Juvenile literature; Children; Education -- Cross-cultural studies -- Juvenile literature; Education; Children -- Cross-cultural studies; Education -- Cross-cultural studies; Cross-cultural studies; Juvenile works